Native bacteria from a Mediterranean greenhouse associated to soil health and suppressiveness - Marín-Guirao, Jose Ignacio; de Cara-García, Miguel (Frontiers in Microbiology, 2025)
This study, conducted over two consecutive seasons in an organic-certified Mediterranean tomato greenhouse, aimed to assess the dynamics of soil bacterial composition at pre-planting phase following the incorporation of fresh sheep manure and subsequent solarisation (biosolarisation), as well as at the end of the crop cycle. Gene sequencing using 16S rRNA, and plate culture methods were applied. Additionally, dual culture tests were performed to evaluate the antagonistic activity of 95 soil-isolated bacteria against five soilborne pathogenic fungi and five beneficial fungi sourced from commercial products. Culturable and thermophilic bacterial populations shifted over time, but showed no clear trend. However, alpha diversity was lower at pre-planting phase and increased by the end of the cropping seasons. Significant shifts in beta diversity were also observed across sampling times. Firmicutes showed higher relative abundance at pre-planting phase, while Proteobacteria were consistently more abundant at the end of the cropping season. The genera Bacillus and Thauera were identified as biomarkers, with Bacillus associated with the pre-planting phase and Thauera with the end of the cropping seasons (LDA score > 4.5). Among the 52 ecological pathways detected via FAPROTAX database, nitrogen-related functions showed higher presence at the end of the cropping seasons. Isolates with antagonistic activity were detected at all sampling times. The 37.9% of the isolates showed antagonism, 31.6% against phytopathogenic fungi, 20.0% against beneficial fungi, and 12.6% against both. Colletotrichum gloeosporioides and Botrytis cinerea were the pathogens to which the highest number of isolates showed antagonism, while Trichoderma asperellum and T. atroviride were among the beneficial ones. Among the native antagonistic bacteria, Streptomyces spp. was the dominant genus followed by Bacillus. This information highlights how the functional diversity of native bacteria communities from biosolarised soils, may impact the performance of introduced biocontrol microorganisms, as well as the development of natural soil suppressiveness.